Diamond Dealers and Feather Merchants - KLOTZ. author. aut Link
X, 120 p. 42 illus.
Keywords: To paraphrase Saul Bellow, it is extremely difficult to escape from the conceptual bottles into which we have been processed, or even to become aware that we are confined within them. Anthro pocentrism, an ancient tradition, is an intellectual constraint that has continually impeded objective probing of the universe around and within us. We are probably born with that constriction, perhaps as a result of evolutionary selection or because each of us has been created in the image of the Deity. But it is only the core of our mental "gestalt. " Around it we find additional shells of intellectual obstruc tions deposited by accretion from our family, our teachers, our experi ences and the society in which we are immersed. It is very hazardous to embrace novel scientific ideas. Personal and social experiences show that the vast majority turn out to be failures. What standards can one use to make judgments? There is a universal tendency to rely on "common sense; " but as Einstein pointed out, this is a collection of views, sensible or not, imprinted in us before the age of sixteen. I have found it a challenge to convince young students that much of what they are certain about and, in fact, correct about, is actually contrary to common sense. For example, on any bright day, anyone who is not blind or an idiot can see the sun literally moving around the earth, from east to west.